2016
DOI: 10.1007/s11255-016-1382-0
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study in the USA of the epidemiology and quality of life of underactive bladder symptoms

Abstract: Underactive bladder symptoms are common and can have a significant impact on ones QOL, although awareness is still lacking among potentially affected individuals. More must be done to allow one to better differentiate between UAB and conditions that are clinically similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Consistent with the high prevalence of UAB symptoms, the risk factors for DU are common and include age, diabetes, cardiovascular disease, and neurologic impairment . General awareness of this condition and symptom overlap with BOO have made it difficult to detect when urinary symptoms are caused by DU . As awareness improves, it will be prudent that physicians accurately screen and treat curable causes of UAB before detrusor contractile failure occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the high prevalence of UAB symptoms, the risk factors for DU are common and include age, diabetes, cardiovascular disease, and neurologic impairment . General awareness of this condition and symptom overlap with BOO have made it difficult to detect when urinary symptoms are caused by DU . As awareness improves, it will be prudent that physicians accurately screen and treat curable causes of UAB before detrusor contractile failure occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, underactive bladder (UAB) is a symptom complex suggestive of DU, and UAB is characterized by prolonged urination time with or without a sensation of incomplete bladder emptying, hesitancy, reduced sensation on filling, and a slow stream . A recent study demonstrated that UAB has a significant impact on the quality of life (QOL) of elderly people in the US . Until now, various hypotheses have been proposed to explain the mechanisms underlying DU, including myogenic and neurogenic dysfunction of the lower urinary tract.…”
Section: Introductionmentioning
confidence: 99%
“…Voiding-associated symptoms describing UAB are associated with impaired quality of life, and as severity of UAB symptoms increase, symptoms of frequency, urgency, and incontinence increase in prevalence as well [3]. It is therefore useful to reconsider UAB in the context of the traditional division of bladder function into “urine storage” and “urine voiding.” Normal bladder filling sensations have been formally described as “the individual is aware of bladder filling and increasing sensation up to a strong desire to void [7].…”
Section: Uab As a Symptom Complexmentioning
confidence: 99%
“…Since then the term has assumed a variety of connotations, all containing the broad implication of impaired voiding. Even within the past year, it has variably been used as a symptom descriptor [3], a statement on bladder function (including as a synonym for DU) [4], and a pathophysiologic concept [5]. This kind of linguistic imprecision risks robbing the term of value.…”
Section: Introductionmentioning
confidence: 99%